Corticosteroids and insulin upregulate the cardiac L-type Ca2+ current and increase the expression of the L-type Ca2+ channel alpha C-1-subunit in rat cardiomyocytes - Rudakova, Elena; Wagner, Michael; Volk, Tilmann (2016)
EVALuna2:214664

Lipid rescue reverses the bupivacaine-induced block of the fast Na+ current (INa) in cardiomyocytes of the rat left ventricle - Wagner, Michael; Zausig, York A.; Ruf, Simone; Rudakova, Elena; Gruber, Michael; Graf, Bernhard M.; Volk, Tilmann (Anesthesiology, 2014)
Cardiovascular resuscitation upon intoxication with lipophilic ion channel-blocking agents has proven most difficult. Recently, favorable results have been reported when lipid rescue therapy is performed, i.e., the infusion of a triglyceride-rich lipid emulsion during resuscitation. However, the mechanism of action is poorly understood.The authors investigate the effects of a clinically used lipid emulsion (Lipovenös® MCT 20%; Fresenius Kabi AG, Bad Homburg, Germany) on the block of the fast Na current (INa) induced by the lipophilic local anesthetic bupivacaine in adult rat left ventricular myocytes by using the whole cell patch clamp technique.Bupivacaine at 10 µm decreased INa by 54% (-19.3 ± 1.9 pApF vs. -42.3 ± 4.3 pApF; n = 17; P < 0.001; VPip = -40 mV, 1 Hz). Addition of 10% lipid emulsion in the presence of bupivacaine produced a 37% increase in INa (-26.4 ± 2.8 pApF; n = 17; P < 0.001 vs. bupivacaine alone). To test whether these results could be explained by a reduction in the free bupivacaine concentration by the lipid (lipid-sink effect), the authors removed the lipid phase from the bupivacaine-lipid mixture by ultracentrifugation. Also, the resulting water phase led to an increase in INa (+19%; n = 17; P < 0.001 vs. bupivacaine), demonstrating that part of the bupivacaine had been removed during ultracentrifugation. The substantially less lipophilic mepivacaine (40 µm) reduced INa by 27% (n = 24; P < 0.001). The mepivacaine-lipid mixture caused a significant increase in INa (+17%; n = 24; P < 0.001). For mepivacaine, only a small lipid-sink effect could be demonstrated (+8%; n = 23; P < 0.01), reflecting its poor lipid solubility.The authors demonstrate lipid rescue on the single-cell level and provide evidence for a lipid-sink mechanism.
EVALuna2:4497

Localization of Kv4.2 and KChIP2 in lipid rafts and modulation of outward K+ currents by membrane cholesterol content in rat left ventricular myocytes - Rudakova, Elena; Wagner, Michael; Frank, Magdalena; Volk, Tilmann (Pflügers Archiv: European Journal of Physiology, 2015)
Lipid rafts are cholesterol-enriched microdomains of the cell membrane. Here we investigate the localization of the pore forming K(+)-channel ?-subunit Kv4.2 and the ?-subunit KChIP2, underlying the transient outward K(+) current (I to), in lipid rafts in left ventricular myocytes. Furthermore, we explored the impact of membrane cholesterol depletion (using 20 mM methyl-beta-cyclodextrin (MBCD)) on K(+) outward currents. Cholesterol-saturated MBCD (20 mM) served as control. Myocytes were isolated from the left ventricular free wall of Wistar rats. The Triton X-100 (4 °C) insoluble fraction of whole cell protein was analyzed by sucrose density gradient centrifugation followed by Western blot. Kv4.2 and KChIP2 were partially detected in low-density fractions (lipid rafts). MBCD treatment (5 min) resulted in a shift of Kv4.2 and KChIP2 towards high-density fractions. K(+) currents were assessed by whole-cell patch-clamp. MBCD treatment resulted in a 29 ± 3 % decrease in I to (20.0 ± 1.6pApF(-1) vs. 28.5 ± 2.0pApF(-1), n = 15, p < 0.001, V Pip = 40 mV) within 5 min. Control solution resulted in a significantly smaller reduction in I to (17 ± 3 %, p < 0.001, p < 0.01 compared with MBCD). MBCD induced a 38 ± 9 % increase in the non-inactivating current component (I sus) (10.1 ± 0.6pApF(-1) vs. 7.6 ± 0.4pApF(-1), n = 15, p < 0.001). This effect was absent in control solution. The increase in I sus was not sensitive to 100 ?M 4-aminopyridine or 20 mM tetraethylammonium, making a contribution of Kv1.5 or Kv2.1 unlikely. In conclusion, in rat ventricular cardiomyocytes, a fraction of Kv4.2 and KChIP2 is localized in lipid rafts. Membrane cholesterol depletion results in 12 % net reduction of I to, a redistribution of the channel proteins Kv4.2 and KChIP2 and an increased delayed rectifier current.
EVALuna2:4522

Rapid Pacing Decreases L-type Ca2+ Current and Alters Cacna1c Isogene Expression in Primary Cultured Rat Left Ventricular Myocytes - Ritzer, Anne; Röschl, Tobias; Nay, Sandra; Rudakova, Elena; Volk, Tilmann (Journal of Membrane Biology, 2023)
The L-type calcium current (ICaL) is the first step in cardiac excitation–contraction-coupling and plays an important role in regulating contractility, but also in electrical and mechanical remodeling. Primary culture of cardiomyocytes, a widely used tool in cardiac ion channel research, is associated with substantial morphological, functional and electrical changes some of which may be prevented by electrical pacing. We therefore investigated ICaL directly after cell isolation and after 24 h of primary culture with and without regular pacing at 1 and 3 Hz in rat left ventricular myocytes. Moreover, we analyzed total mRNA expression of the pore forming subunit of the L-type Ca2+ channel (cacna1c) as well as the expression of splice variants of its exon 1 that contribute to specificity of ICaL in different tissue such as cardiac myocytes or smooth muscle. 24 h incubation without pacing decreased ICaL density by 10% only. Consistent with this decrease we observed a decrease in the expression of total cacna1c and of exon 1a, the dominant variant of cardiomyocytes, while expression of exon 1b and 1c increased. Pacing for 24 h at 1 and 3 Hz led to a substantial decrease in ICaL density by 30%, mildly slowed ICaL inactivation and shifted steady-state inactivation to more negative potentials. Total cacna1c mRNA expression was substantially decreased by pacing, as was the expression of exon 1b and 1c. Taken together, electrical silence introduces fewer alterations in ICaL density and cacna1c mRNA expression than pacing for 24 h and should therefore be the preferred approach for primary culture of cardiomyocytes. Graphical Abstract: [Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2023-04-14
Keywords: Cacna1c; Cardiac memory; Regional differences; Remodeling

Transcriptional regulation of the L-type Ca2+ channel alpha C-1-subunit by corticosteroid - Ritzer, Anne; Rudakova, Elena; Volk, Tilmann (2017)
EVALuna2:214662